Locating a γ-ray source using cuboid scintillators and the KNN algorithm - Du, Te; Zhao, Zijia; Zhu, Qingjun; Tian, Lichao (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2021)
In using radiation detectors to locate γ-ray sources, one needs to consider not only the detection efficiency, but also the portability of the detector and the detectable energy range. In this paper, we put forward a novel proposal which combines the advantages of cuboid scintillators and array detectors, in order to achieve portability and efficiency. To this aim, we first developed a mathematical angular response model of cuboid scintillators, and then verified the model experimentally. Then, we designed a simple structured detector array and used the Monte Carlo simulations to verify its angular resolution. Monte Carlo results show that the angular resolution of the detector array may achieve one degree. Finally, in order to further improve the detector performance, we implemented the KNN algorithm, achieving an angular resolution of the order of one tenth of a degree.